Analysis of Customer Satisfaction Level towards Product Quality of Chicken Slaughter House of PT. Ciomas Adisatwa Maros, South Sulawesi - H. Khurniyah; A. A. Amrawaty; M. Aminawar (Jurnal Ilmu dan Teknologi Peternakan, 2016)
The purpose of research was to study the level of customer satisfaction towards product quality of the slaughter house of PT. Ciomas Adisatwa. The study was conducted on the customers of the company who have been transacting over one year. This research was a descriptive quntitative research with explanatory research design. The number of samples was  84 customers of the Ciomas Adisatwa slaughter house, consisting of five fast food restaurantcustomers, four supermarkert customers, eight trading customers, 10 wet markert customers and 57 Horeka customers. Data were analyzed using Importance Performance Analysis (IPA) and Customer Sataisfaction Index (CSI). The results showed that in order to satisfy its customers, PT Ciomas Adistwa slaughter house need to pay attention on the attributes in the first quadrant, namely the hygiene of products, response on the product complaint, easiness in obtaining the product, and facilities provided by the company. In general, the customers were quite satisfied with the performance and product quality of PT Ciomas Adisatwa slaughter house. This was based on the CSI score of 62.4% out of the scale of  51-65%.